2016
DOI: 10.1007/s11356-016-6112-8
|View full text |Cite
|
Sign up to set email alerts
|

No-tillage effects on N and P exports across a rice-planted watershed

Abstract: No tillage (NT) can be used as a management tool to alleviate the negative effects of agricultural practices on the environment by reducing the runoff volume and nutrient exports. The main objective of this research was to quantify the effect of NT on nitrogen (N) and phosphorus (P) exports across a rice-planted watershed using the soil and water assessment tool (SWAT) model. Results show that total N and P runoff exports from rice fields across the watershed ranged from 7.2 to 22.8 kg N/ha and 0.56 to 6.80 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The reason for the low levels of N and P movement along the soil profile under the conservation tillage technique was probably due to the latter's ability to reduce surface runoff and infiltration, thereby allowing most of the nutrients to be concentrated at the 0-20 cm soil depth. According to Liang et al [34], a decrease in runoff was observed in the NT system compared with the CT system, ranging from 16.0 to 37.3% (average 25.9%), from 2008 to 2012, demonstrating a declining rate. The corresponding rates of TN and TP exports varied from 4.1 to 16.9% (average 8.5%) and from 5.6 to 10.3% (average 7.8%), respectively, for NT compared with results for CT [34].…”
Section: N and P Movement Along The Soil Profile (0-100 Cm)mentioning
confidence: 98%
See 3 more Smart Citations
“…The reason for the low levels of N and P movement along the soil profile under the conservation tillage technique was probably due to the latter's ability to reduce surface runoff and infiltration, thereby allowing most of the nutrients to be concentrated at the 0-20 cm soil depth. According to Liang et al [34], a decrease in runoff was observed in the NT system compared with the CT system, ranging from 16.0 to 37.3% (average 25.9%), from 2008 to 2012, demonstrating a declining rate. The corresponding rates of TN and TP exports varied from 4.1 to 16.9% (average 8.5%) and from 5.6 to 10.3% (average 7.8%), respectively, for NT compared with results for CT [34].…”
Section: N and P Movement Along The Soil Profile (0-100 Cm)mentioning
confidence: 98%
“…According to Liang et al [34], a decrease in runoff was observed in the NT system compared with the CT system, ranging from 16.0 to 37.3% (average 25.9%), from 2008 to 2012, demonstrating a declining rate. The corresponding rates of TN and TP exports varied from 4.1 to 16.9% (average 8.5%) and from 5.6 to 10.3% (average 7.8%), respectively, for NT compared with results for CT [34]. The soil TN, NO 3…”
Section: N and P Movement Along The Soil Profile (0-100 Cm)mentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Clausen et al studied tillage effects on runoff for croplands in Vermont, USA, and found that reduced tillage reduced runoff by 64% [45]. Liang et al reported that runoff volume from rice-planting watersheds was reduced by 25.9% using no-tillage techniques [46]. Reduced tillage and no-tillage reduce the intensity of tillage practices as well as the impact of rain by the protection of soil surface using crop residues.…”
Section: Conservation Tillagementioning
confidence: 99%